2019
DOI: 10.3174/ajnr.a6195
|View full text |Cite
|
Sign up to set email alerts
|

PACS Integration of Semiautomated Imaging Software Improves Day-to-Day MS Disease Activity Detection

Abstract: BACKGROUND AND PURPOSE: The standard for evaluating interval radiologic activity in MS, side-by-side MR imaging comparison, is restricted by its time-consuming nature and limited sensitivity. VisTarsier, a semiautomated software for comparing volumetric FLAIR sequences, has shown better disease-activity detection than conventional comparison in retrospective studies. Our objective was to determine whether implementing this software in day-today practice would show similar efficacy. MATERIALS AND METHODS: VisTa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…Second, we observed that the use of lesion masks produced by the lesion detection module significantly increases the number of lesions detected regardless of the level of expert's experience (more than 15% more lesions with the MUSIC workflow than without). This observation is in line with recent studies not involving deep learning based segmentation (26)(27)(28). In parallel, while not significant, we also observed a natural reduction of the inter-expert variability when using the segmentation masks.…”
Section: Automated New Lesion Segmentation Tools Provide a Relevant And Valuable Aid For Clinicianssupporting
confidence: 93%
“…Second, we observed that the use of lesion masks produced by the lesion detection module significantly increases the number of lesions detected regardless of the level of expert's experience (more than 15% more lesions with the MUSIC workflow than without). This observation is in line with recent studies not involving deep learning based segmentation (26)(27)(28). In parallel, while not significant, we also observed a natural reduction of the inter-expert variability when using the segmentation masks.…”
Section: Automated New Lesion Segmentation Tools Provide a Relevant And Valuable Aid For Clinicianssupporting
confidence: 93%
“…We routinely used semi-automated co-registration fusion software to compare 3D FLAIR sequences of the brain, while the aforementioned studies used 2D axial proton density and T2-weighted sequences, which likely resulted in a higher number of new BLs detected in our study. 27,28,30 Differences in MRI field strengths (3T in our study vs 1.5T in some of the studies) may have also contributed to the discrepant results. 31 Interestingly, we did not see a higher yield of CSLs even with the inclusion of PSIR sequence in our SC-MRI protocol, an MRI sequence thought to be more sensitive than the T2-weighted and proton density (PD) sequences used in the prior studies.…”
Section: Discussioncontrasting
confidence: 58%
“…Although structured reporting is not routinely done, it is common practice for the neuroradiologists in our institution to indicate the number and location of new lesions in the report. In rare occasions where the exact number was not provided in the report, the images were re-evaluated, and the number of new lesions was counted and recorded by two neuroradiologists experienced in MS. A semi-automated co-registration fusion software with color overlay 27,28 for comparing volumetric FLAIR sequences of the brain (Volume Matching, Carestream Health; Rochester, NY) was routinely used in our practice during the study period in addition to conventional review of the images. Studies that were reported as equivocal for new lesions were reviewed in consensus by two neuroradiologists with 5- and 10-year experience for final determination of the presence or absence of new lesions or exclusion due to technical factors (poor image quality of current and prior study).…”
Section: Methodsmentioning
confidence: 99%
“…Subtraction of magnetic resonance (MR) images has been described in multiple sclerosis to enhance detection of contrast enhancing lesions, estimate lesion volume change, 1 or assess new lesions in longitudinal follow-up. 2 Subtraction of images requires dedicated software not readily available at all imaging centers. Here, we present a simple technique that instead of subtraction utilizes overlaid semi-transparent greyscale volume images from two different time points, namely, routine follow-up.…”
Section: Introductionmentioning
confidence: 99%